Sigmoid volvulus, acquired megacolon and pseudo-obstruction. Issue 8 (August 2017) - Kallam, Ramana R.; Bandyopadhyay, Dibyendu
Abstract: This article is aimed at describing three common colorectal surgical emergencies that present as large bowel obstruction. Emphasis is given to sigmoid volvulus, acquired megacolon/megarectum and colonic pseudo-obstruction with respect to their clinical presentation and management including emergency treatment and any further elective treatment options once the emergency situation is resolved. In western society, these conditions are commonly associated with elderly and institutionalized patients posing significant management challenges. With increasing emphasis on emergency sub-speciality care provision, thorough understanding of these clinical conditions is essential to appropriately tailor the management to individual patient needs.